The spider community in organic cotton crops in southern Spain - PÉREZ-GUERRERO, SERGIO; TAMAJÓN, RAFAEL; ALDEBIS, HANI K.; VARGAS-OSUNA, ENRIQUE (Revista Colombiana de Entomología, 2009)
Compared to traditional management, organic farming provides an alternative to the problems of the appearance of resistance, residues and environmental pollution, as well as favoring an increase in ecosystem biodiversity through beneficial effects on other fauna. In agroecosystems, the combined action of natural enemies on phytophages can maintain populations of many of them below economic damage thresholds. One of the least known groups of predators in studies on the natural control of cotton pests are the spiders (Order Araneae), therefore surveys were conducted in plots of organic cotton situated in southern Spain: Córdoba, Sevilla and Cádiz. Specimens were collected by beating the plants. The most abundant species was Cheiracanthium sp. (Miturgidae), followed by other species such as Philodromus sp. (Philodromidae), the crab spiders Thomisus onustus, Runcinia grammica and Synema globosum (Thomisidae), Salticus sp. (Salticidae) and Larinia lineata (Araneidae). In addition, individuals were collected from the families Theridiidae and Linyphiidae. This work, therefore, is a first step in understanding the species and their abundance in organic cotton crops, and will be the basis for future research in the area of phytophage control by spiders.